Pengaruh Kompensasi, Keselamtan Kerja, dan Kesehatan Kerja Terhadap Kinerja Karyawan di PT Indobaja Primamurni Gresik - Hidayatulloh, Farid; Santoso, Rahmat Agus; Alamudi, Abdul Kadir (Jurnal Mahasiswa Manajemen, 2024)
Background –PT Indobaja Primamurni Gresik is a national private company engaged in the trade of iron and steel construction. Based on employee performance data of PT Indobaja Primamurni Gresik in the last three years, there was a decline in performance from 2018 to 2020. In 2018, the total score of performance assessment indicators reached 93.4%, then decreased to 81.8% in 2019, and decreased again to 70.8% in 2020. This decline in performance is a problem that needs to be further investigated regarding the factors that influence it.Objective –This study aims to analyze the effect of compensation, occupational safety, and occupational health on employee performance at PT Indobaja Primamurni Gresik.Design / Methodology / Approach –The research method used is quantitative with an associative approach. The research population consisted of 179 employees, with the sampling technique using saturated sampling. Data collection was carried out through questionnaires. Data analysis used multiple linear regression.Findings –The results showed that: (1) Compensation has a positive and significant effect on employee performance, (2) Occupational safety has a positive and significant effect on employee performance, (3) Occupational health has a positive and significant effect on employee performance.Research Implication –The implication of this research is that companies need to pay attention to aspects of compensation, occupational safety, and occupational health to improve employee performance.Limitations –This research was only conducted at a steel producing company and used several limited variables so that it did not cover all important aspects in assessing employee performance.